OPTIMAL ELECTROPORATION CONDITION FOR SPERM MEDIATED GENE TRANSFER IN STRIPPED CATFISH (Pangasionodon hypophthalmus) - Raden Roro Sri Pudji Sinarni Dewi; Alimuddin Alimuddin; Agus Oman Sudrajat; Komar Sumantadinata; Sularto Sularto (Indonesian Aquaculture Journal, 2010)
The success of transgenic fish production has been achieved through eggs fertilization using electroporated sperms carrying exogenous DNA. This study was conducted in order to obtain the optimal electroporation condition for stripped catfish sperm. A plasmid containing green fluorescent protein (GFP) gene driven by carp β-actin promoter was transferred into sperm using electrophoresis method towards transgenic stripped catfish (Pangasionodon hypophthalmus) production. Electroporation was carried out using square wave shock with pulse length of 30 ms and pulse interval of 0.1 sec. Treatments are combination between voltage (50 V, 75 V, and 100 V) and pulse number (1 and 3). Exogenous DNA concentration used was 10 μg/mL of Tris-EDTA. Results showed that increasing the voltage from 50 to 100 decreased sperm motility, while pulse number did not affect sperm motility. Voltage of 50 gave the best motility of sperm, although sperm viability relatively similar between treatments and control except at 100 V with 3 pulses number. Further, electroporation-treated sperms were able to fertilize eggs. Higher hatching rate of eggs was obtained in electroporation treatment at 50 V with pulse number of 1 and 3. The persistence of transferred GFP was detected in electroporated and incubated sperms (control). However, GFP was only detected in larvae from eggs that were fertilized by electroporated sperm. Thus, electroporation could be applied to produce transgenic stripped catfish.